‘Fairytale Princess’ and ‘Red Hot’ — Red Lance-leaved Caladium Cultivars - Zhanao Deng (EDIS, 2013)
Caladiums are valued in landscapes and containers for their colorful and variable-shaped leaves. Two types of caladium cultivars exist in commercial production: fancy- and lance-leaved. ‘Florida Sweetheart’ is the most popular lance-leaved commercial cultivar of all colors. It produces wide lance leaves with a rosy color and relatively large tubers. ‘Florida Red Ruffles’ is the most popular red, lance-leaved commercial cultivar among caladium growers, greenhouse growers, and nurseries. It has excellent sunburn tolerance. Both cultivars were introduced by the University of Florida (UF) caladium breeding program. This 9-page fact sheet was written by Zhanao Deng, and published by the UF Department of Environmental Horticulture, August 2013.